ROLLING EXPERIMENT WITH PARTIALLY MOLTEN ROCKS: A NEW APPARATUS AND SOME EXPERIMENTS ON THE KINETICS OF MATERIAL TRANSPORT, DISSOLUTION AND CRYSTAL GROWTH - Ikeda S.; Nakashima S. (My University, 1999)
In order to investigate the effects of melt movement on material transport, dissolution and crystal growth in partially molten rock systems, a new apparatus was designed to move partial melt. Spherical specimens with low degrees of melting (less than 40 vol%) were rolled in a PtRh crucible rotating at 240 rpm in an electric furnace. Melt movement in this rolling experiment was confirmed by the displacement of Au powder added to the partially molten natural dacite. A partial melt movement of about 200 μm/h was observed in the rolling experiment. Element transport in the melt was traced using a Ni foil placed in the centre of the spherical dacite specimens. The apparent diffusion coefficient of Ni in the rolling experiment (1 x 10-12 m2/s) was one order of magnitude larger than the diffusion coefficient in the static experiment (1 x 10-13 m2/s). An increase of the dissolution rate of crystals of ~ 20% was observed under these advective conditions. The calculated dissolution rates using diffusion coefficients and the thicknesses of compositional boundary layers in melt showed good agreement with the observed dissolution rates. This suggests that dissolution in the present study was transport-controlled and was enhanced by rolling. Furthermore, an increase in crystal growth rate was observed in an isothermal experiment using a partially molten synthetic pyroxene solid solution. These results indicate that the kinetics of dissolution and the growth of crystals are influenced by melt movement in partially molten rock systems in which advective material transport is larger than material transport resulting solely from molecular diffusion.